VaR - optymalny liniowy portfel inwestycyjny z ograniczeniami - Iskra, Daniel (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents the optimization of securities portfolio process with constraints. Taking into account the VaR the optimization concerns the value's portfolio structure. Two strategies are considered by the author:- setting a VaR the minimization of the probability that the VaR excide the value,- setting a probability level the minimization of VaR value.First strategy enables building the portfolio structure which value would be less than the value settled by the investor with minimal probability. Second strategy begins with setting probability α. Next step is to build such a portfolio structure that the value limit beneath which the portfolio value would not decrease (with probability l-α) will be at the maximum level. In both cases the required drift of the securities portfolio should not be lower than determined earlier. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 194-202